As varas empresariais do Tribunal de Justiça de São Paulo: os impactos no tempo médio processual, na qualidade das decisões e na previsibilidade dos julgamentos em matéria empresarial - Nani, Ana Paula Ribeiro (2023)
The judicial specialization in business law matters is a recent recommendation (n. 56/2019) of the National Council of Justice (CNJ) for all courts in the national territory. At the Court of Justice of the State of São Paulo (TJSP), this specialization in business matters began in 2005, and has more recently culminated with the installation of two Business and Arbitration-Related Disputes Lower Courts in the judicial district of the Capital (in December 2017) and two Business and Arbitration-Related Disputes Lower Courts in the 1st Judicial Administrative Region – “1st RAJ” (in December 2019), the latter ones with jurisdiction to serve the entire Greater São Paulo area, except the Capital. These Business Lower Courts installed in São Paulo (two in the Capital and two in the 1st RAJ) have not only been referenced as an "example" / "model" for the Courts of other States, but, considering them as a "successful" experience and with "good results" , the intention is to proceed with the expansion throughout the State of São Paulo, with the installation of Business Lower Courts in other regions of the State. Despite of such mobilization, no public academic studies were found that analyze the results of such Business Lower Courts already installed by the TJSP. The purpose of this research is to investigate, based on the "case study" methodology, to what extent the Business Lower Courts of the Court of Justice of São Paulo that have been installed so far (Capital and 1st RAJ) have achieved the objectives that were targeted with their creation (specifically: greater speed in providing jurisdiction, higher quality of decisions and greater predictability in business-related judgments). For the limits of this research, it was sought, in short a) to understand, by means of bibliographical research, judicial specialization - in order to ascertain which are the criteria and the models for specializing jurisdictional activity, as well as to identify which are the expected advantages of specialization and if there are disadvantages or controversial aspects that compromise its acclaim as an "irremediable measure for the improvement of judicial provision" (as stated in the Resolutions that gave rise to the creation of the Business Lower Courts object of this study ); b) to investigate, specifically, the processes of creation of the Business Lower Courts in TJSP, in order to ascertain the context and the objectives claimed to justify such creations; c) to analyze, by means of an empirical analysis of quantitative data (when feasible) and of the perceptions (collected through interviews) of the players that are involved with the Business Lower Courts (lawyers, magistrates and court servers), the impacts of the specialization especially in the average process time, in the quality of the decisions and in the predictability of the business judgments; and, finally, d) to examine to what extent, as it has been disseminated in the legal environment, the Business Lower Courts at TJSP have, in fact, reached the objectives set when they were implemented.